The effects of six-weeks change of direction speed and technique modification training on cutting performance and movement quality in male youth soccer players - dos Santos, T.; McBurnie, A.; Comfort, P.; Jones, P. A. (Sports, 2019)
Cutting manoeuvres are important actions associated with soccer performance and a key action associated with non-contact anterior cruciate ligament injury; thus, training interventions that can improve cutting performance and movement quality are of great interest. The aim of this study, therefore, was to determine the effects of a six-week change of dire[ction (COD) speed and technique modification training intervention on cutting performance and movement quality in male youth soccer players (U17s, n = 8) in comparison to a control group (CG) (U18s, n = 11) who continued `normal` training. Cutting performance was assessed based on completion time and COD deficit, and the field-based cutting movement assessment score (CMAS) qualitative screening tool was used to assess cutting movement quality. Significant main effects for time (pre-to-post changes) (p = 0.041, ?2 = 0.224-0.839) and significant interaction effects of time and group were observed for cutting completion times, COD deficits, and CMASs. Improvements in completion time (p < 0.001, g = 1.63-1.90, -9% to -11% vs. -5% to 6%) and COD deficit (p = 0.012, g = -1.63 to -2.43, -40-52% vs. -22% to -28%) for the COD intervention group (IG) were approximately two-times greater than the CG. Furthermore, lower CMASs (i.e., improved cutting movement quality) were only observed in the IG (p = 0.025, g = -0.85 to -1.46, -23% to -34% vs. 6-19%) compared to the CG. The positive changes in CMASs were attributed to improved cutting technique and reduced incidences of high-risk deficits such as lateral trunk flexion, extended knee postures, knee valgus, hip internal rotation, and improved braking strategies. The results of this study indicate that COD speed and technique modification training, in addition to normal skills and strength training, improves cutting performance and movement quality in male youth soccer players. Practitioners working with male youth soccer players should implement COD speed and technique modification training to improve cutting performance and movement quality, which may decrease potential injury-risk.